2012
DOI: 10.1007/s00401-012-1031-3
|View full text |Cite
|
Sign up to set email alerts
|

Frequent ATRX mutations and loss of expression in adult diffuse astrocytic tumors carrying IDH1/IDH2 and TP53 mutations

Abstract: Gliomas are the most common primary brain tumors in children and adults. We recently identified frequent alterations in chromatin remodelling pathways including recurrent mutations in H3F3A and mutations in ATRX (α-thalassemia/mental-retardation-syndrome-X-linked) in pediatric and young adult glioblastoma (GBM, WHO grade IV astrocytoma). H3F3A mutations were specific to pediatric high-grade gliomas and identified in only 3.4 % of adult GBM. Using sequencing and/or immunohistochemical analyses, we investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
303
4
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 372 publications
(340 citation statements)
references
References 33 publications
21
303
4
3
Order By: Relevance
“…As expected [15,21,38], ATRX was among the top genes with higher expression in astrocytic versus oligodendroglial tumors as well as 1p/19q intact versus 1p/19q co-deleted tumors (Supplementary Tables 9-10). …”
Section: Molecular Correlates Of Glioma Type and Who Gradesupporting
confidence: 70%
See 2 more Smart Citations
“…As expected [15,21,38], ATRX was among the top genes with higher expression in astrocytic versus oligodendroglial tumors as well as 1p/19q intact versus 1p/19q co-deleted tumors (Supplementary Tables 9-10). …”
Section: Molecular Correlates Of Glioma Type and Who Gradesupporting
confidence: 70%
“…Array-CGH data were evaluated as reported before using aCGHPipeline [21]. Gene expression data were analyzed after reduction to metagenes using self-organizing map (SOM) machine learning [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, mutations and (consequently) loss of expression of alpha-thalassemia/mental retardation syndrome X-linked (ATRX) have been reported in one third of pediatric glioblastomas [20] and 7% of adult glioblastomas [7]. Virtually all mutations are inactivating and lead to a loss of protein expression [7,15]. Mechanistically, loss of ATRX and death-domain associated protein (DAXX) are important factors for a telomere maintenance mechanism not involving telomerases (alternative lengthening of telomeres (ALT)).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies have reported frequent ATRX loss (but not DAXX loss) in astrocytoma, leiomyosarcoma, dedifferentiated liposarcoma and other tumor types, and the loss of ATRX has been highly correlated with the alternative lengthening of telomeres phenotype. 6,12,13,[17][18][19][20][21] However, knockdown of ATRX or DAXX has not led to alternative lengthening of telomeres, and patients with germline ATRX mutations do not appear to be cancer prone. 18,22 In addition, although loss of either ATRX or DAXX is perfectly associated with alternative lengthening of telomeres in pancreatic neuroendocrine tumors, the situation is more complex in sarcomas.…”
mentioning
confidence: 99%